The Role of Dendritic Mesoporous Silica Nanoparticles' Size for Quantum Dots Enrichment and Lateral Flow Immunoassay Performance. Issue 4 (2nd February 2021) - Gao, Fang; Liu, Yang; Lei, Chang; Liu, Chao; Song, Hao; Gu, Zhengying; Jiang, Pei; Jing, Sheng; Wan, Jingjing; Yu, Chengzhong
Abstract: Using dendritic mesoporous silica nanoparticles (DMSNs) for quantum dots (QDs) enrichment and signal amplification is an emerging strategy for improving the detection sensitivity of lateral flow immunoassay (LFIA). In this study, a new and convenient approach is developed to prepare water‐dispersible DMSNs‐QDs. A series of DMSNs with various diameters (138, 251, 368, and 471 nm) are studied for loading QDs and LFIA applications. The resultant water‐dispersible DMSNs‐QDs exhibit a high fluorescence retention of 81.8%. The increase in particle size from 138 to 471 nm results in an increase in loading capacity of QDs and a decrease in binding quantity of the DMSNs‐QDs in the test line of LFIA. This trade‐off leads to an optimal DMSNs‐QDs size of 368 nm with a limit of detection reaching 10 pg mL −1 (equivalent to 9.0 × 10 −14 m ) for the detection of C‐reactive protein, which is nearly an order of magnitude more sensitive than the literature. To the best of the authors' knowledge, this study is the first to demonstrate the distinctive role of DMSN's size for QDs enrichment and LFIA. The strategy developed from this work is useful for the rational design of high‐quality QDs‐based nanoparticles for ultrasensitive detection. Abstract : The distinctive role of dendritic mesoporous silica nanoparticles' (DMSNs) size for quantum dots (QDs) enrichment and lateral flow immunoassay (LFIA) is investigated for the first time. 368 nm DMSNs‐QDs labelled LFIA displays a limit of detection of 10 pg mL –1 for the detection of C‐reactive protein, which is nearly an order of magnitude more sensitive than the literature.